`y = (x+5)(x-2)` Write the quadratic function in standard form.
Standard form refers to the ax^2+bx+c format, where a, b, and c are the coefficients of each of the elements in the quadratic equation.
Basically, you want to FOIL the two binomials to obtain your quadratic. You can do this but multiplying the First, Outside, Inside, Last, then adding them together like so:
First = a*c
Outside = a*d
Inside = b*c
Last = b*d
Thus, your result is a*c+a*d+b*c+b*d.
In the case of your problem, this results in:
`y = (x+5)(x-2)`
`y = (x^2+(-2x)+5x-10)`
The standard form of a quadratic function is `ax^2+bx+c=0` , to change the above to standard form we can simplify it:
`y = (x + 5)(x - 2)`
`y = (x^2 - 2x + 5x - 10)`
`y = x^2 + 3x - 10`
where a = 1, b = 3 and c = -10